GCKR Polymorphisms Increase the Risks of Low Bone Mineral Density in Young and Non‐Obese Patients With MASLD and Hyperuricemia - Tzu‐Hao Li; Yu‐Shin Huang; Chia‐Chen Ma; Shin‐Yu Tsai; Hung‐Cheng Tsai; Hsiao‐Yun Yeh; Hsiao‐Chin Shen; Shiao‐Ya Hong; Chien‐Wei Su; Hwai‐I Yang; Ying‐Ying Yang; Ming‐Chih Hou (Kaohsiung Journal of Medical Sciences)
ABSTRACT Metabolic‐associated steatotic liver disease (MASLD) encompasses common comorbidities including low bone mineral density (BMD) and hyperuricemia (HU), yet relevant genetic analyses are limited. This study aimed to investigate the genetic effects of risk single nucleotide polymorphisms (SNPs) on the occurrence of low BMD in patients with MASLD and HU, particularly focusing on relatively young or non‐obese populations. We conducted a cross‐sectional study utilizing data from the Taiwan Biobank, screening a total of 150,709 participants who were prospectively enrolled over a period of 13 years. The risk SNPs for MASLD were identified. Genotype analyses of HU and its effects on the occurrence of low BMD in the general population were evaluated, with further analyses of common SNPs focusing on patients with MASLD, including subgroup analyses on relatively young and non‐obese populations. A total of 20,496 participants were eligible for analysis, including 7526 patients with MASLD. Several risk SNPs for MASLD were identified. Furthermore, MASLD patients carrying the PNPLA3‐rs738409 C_C, PNPLA3‐rs2896019 T_T, GCKR‐rs780094 T_T, and GCKR‐rs1260326 T_T genotypes exhibited an increased risk of comorbidity with HU. Trend analysis revealed that the T alleles in GCKR‐rs780094 and GCKR‐rs1260326 were associated with the occurrence of low BMD in MASLD individuals comorbid with HU, particularly among relatively young or non‐obese populations. In relatively young, non‐obese patients with MASLD and HU, genetic effects significantly increase the risk of occurrence of low BMD. Given the presence of genetic effects in these ostensibly low‐risk groups, heightened awareness and close follow‐up are recommended.